Risk management in trading : techniques to drive profitability of hedge funds and trading desks - Edwards, Davis W. (Hoboken : Wiley, 2014)
"A comprehensive resource for understanding how to minimize risk and increase profits In this accessible resource, Wall Street trader and quantitative analyst Davis W. Edwards offers a definitive guide for nonprofessionals which describes the techniques and strategies seasoned traders use when making decisions. Risk Management in Trading includes an introduction to hedge fund and proprietary trading desks and offers an in-depth exploration on the topic of risk avoidance and acceptance. Throughout the book Edwards explores the finer points of financial risk management, shows how to decipher the jargon of professional risk-managers, and reveals how non-quantitative managers avoid risk management pitfalls.Avoiding risk is a strategic decision and the author shows how to adopt a consistent framework for risk that compares one type of risk to another. Edwards also stresses the fact that any trading decision that isn't based on the goal of maximizing profits is a decision that should be strongly scrutinized. He also explains that being familiar with all the details of a transaction is vital for making the right investment decision. Offers a comprehensive resource for understanding financial risk management Includes an overview of the techniques and tools professionals use to control risk Shows how to transfer risk to maximize results Written by Davis W. Edwards, a senior manager in Deloitte's Energy Derivatives Pricing Center Risk Management in Trading gives investors a hands-on guide to the strategies and techniques professionals rely on to minimize risk and maximize profits"--
CHAPTER 9 Credit Value Adjustments (CVA)Trading is a Social Activity; Credit Risk; Exposure at Default (EAD); Loss Given Default (LGD); Probability of Default (PD); Correlation Between PD and LGD; Credit Limits and Counterparty Exposure; Current Exposure and Potential Future Exposure; Calculating a Credit Value Adjustment; Multi-Period CVA Calculation; Settlement Risk; Test Your Knowledge; Afterword; Answer Key; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Chapter 8; Chapter 9; About the Author; Index; End User License Agreement
Includes index.
Machine generated contents note: Preface Chapter 1: Trading and Hedge Funds Chapter 2: Financial Markets Chapter 3: Financial Mathematics Chapter 4: Backtesting and Trade Forensics Chapter 5: Mark to Market Chapter 6: Value-at-Risk Chapter 7: Hedging Chapter 8: Options, Greeks, and Non-Linear Risks Chapter 9: Credit Value Adjustments (CVA) Afterword Answer Key About the Author Index .
Description based on print version record and CIP data provided by publisher.
Keywords: Risk management; Investment banking; Hedge funds; BUSINESS & ECONOMICS / Corporate Finance; Hedge funds; Investment banking; Risk management; Electronic books